Thermal fatigue analysis of gold wire bonding solder joints in MEMS pressure sensors by thermal cycling tests. (December 2022) - Zhang, Yunfan; Wu, Kangkang; Li, Hui; Shen, Shengnan; Cao, Wan; Li, Feng; Han, Jinzhe
Abstract: Thermal fatigue is one of the main causes of device failure in micro-electro-mechanical systems (MEMS). Gold wire bonding plays the role of electrical connection and signal transmission, which is the key structure of MEMS pressure sensor. In this paper, the fatigue failure of gold wire bonding solder joints caused by the thermal cycling test was studied. The thermal cycling test on MEMS pressure sensor was conducted using a temperature chamber with the cycling temperature range from −40 °C to 150 °C. After 1600 cycles, the solder joints were found with significant resistance increase to about 25 Ω or even overrange value by electrical measurement. In addition, the computed tomography (CT) scanning results showed that the solder joints on the substrate underwent thermal fatigue failure and one joint was separated from the pad with a distance of 36 μm, while the solder joints on the chip were still in good bonding conditions. The mechanism of thermal fatigue failure can be summarized as the thermal mismatch of solder joint materials, residual stress due to the bonding process, and stress concentration caused by the wedge area. Highlights: The resistance variation of bonding pairs during thermal cycling test was investigated. CT scanning results characterized the bonding state after the thermal cycling test. The thermal fatigue of AuAu and AuAg bonding were analyzed.